2022
DOI: 10.1126/sciadv.abn4072
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen activation on Ba-containing perovskite materials

Abstract: Oxygen activation, including oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), is at the heart of many important energy conversion processes. However, the activation mechanism of Ba-containing perovskite materials is still ambiguous, because of the complex four-electron transfer process on the gas-solid interfaces. Here, we directly observe that BaO and BaO 2 segregated on Ba-containing material surface participate in the oxygen activation process via the formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…As in other perovskite materials, such as SrTiO 3 , segregation of BaO might have been expected. Such a process would have resulted in an increase in Ba on the surface changes [ 28 ]. However, O 1s spectra revealed different chemical species and showed that both Ba and Sn spectra might be the result of increasing oxygen deficiency and the difference in cation chemical surroundings, as well as the experimental conditions [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…As in other perovskite materials, such as SrTiO 3 , segregation of BaO might have been expected. Such a process would have resulted in an increase in Ba on the surface changes [ 28 ]. However, O 1s spectra revealed different chemical species and showed that both Ba and Sn spectra might be the result of increasing oxygen deficiency and the difference in cation chemical surroundings, as well as the experimental conditions [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…XRD patterns evidence for the BSMWO-I sample an amorphous structure and for the sample BSMWO-II a nanocrystalline structure containing the XRD peaks typical for the face-centered cubic structure of BaSrMgWO6 and some impurity XRD peaks, located at 2 values of 26.70 º and 27.49 º respectively (noted with * and ** respectively in Figure 1), that generally are attributed to some impurity phases like MeWO4 and Me2WO5 (Me=Ba, Sr, Mg). The presence of some BaO2, SrO2 and MgO phases that may have a contribution to these XRD peaks may be caused by the formation of some under-stoichiometric phases [25][26][27][28][29][30].…”
Section: Structural Investigationmentioning
confidence: 99%
“…As the coordination of negative ions is higher the local electron potential increases and the binding energy decreases [39]. In the stoichiometric perovskite structure Ba is 12-fold and, in the under-stoichiometric structure and in peroxide structure is 10-fold, so the binding energy of Ba 2+ in cubic double perovskite structure will be lower than Ba 2+ in under-stoichiometric Ba2-(x+y) SrxMgy WO5 structure or in tetragonal BaO2 [26,33,40]. The attribution of the peaks with higher binding energy to BaO2 agrees with the results obtained by other authors [33].…”
Section: Chemical Statesmentioning
confidence: 99%
“…Up to now, kinds of UCNPs with different controllable shapes and sizes have been synthesized through hydro‐ and solvothermal methods [ 87–94 ] as well as by thermal decomposition [ 30,95–98 ] and chemical coprecipitation. [ 99–101 ] The luminescence efficiency of the resulting materials was improved significantly by fabricating UCNPs with core–shell structure within one single nanoparticle. [ 37,41,64,102–104 ] Despite these great achievements, designs of currently developed UCNPs must be delicately laid out to take into account their compositions and complex structures.…”
Section: Properties Of Upconversion Nanoparticlesmentioning
confidence: 99%